Relations of China with the leading states of the European Union - Sharypkazy, N.; Arzykulov A. А (Journal of Oriental Studies, 2024)
If today on volume the European Union for China is the second trade partner, and For the European Union China is on the first place. Since 1998 the strategic partnership the People’s Republic of China European Union fruitfully works. At the same time China separately cooperates with the states of the Eurozone. And here the leading states Europy are priority.